IS ASTANA A NATIONALISTIC PROJECT? THE ROLE OF KAZAKHSTAN’S NEW CAPITAL IN DEVELOPMENT OF THE NATIONAL IDENTITY - Kopbayeva, Diana (European Scientific Journal, ESJ, 2013)
Academic literature suggests that transformation of the state power fosters shift in national identity (Verdery, 1999). The capital relocation is one of the reflections of this shifting. This paper explores the role of Kazakhstan’s new capital in nation-building process and Kazakh identity formation. Kazakhstan obtained its independence after disintegration of the Soviet Union in 1991; 6 years later in December1997 the President moved the capital from Almaty to small town in the North Aqmola (Astana). The government did not provide convincing explanations for the relocation, which caused people and international observers to develop various theories about the real meaning of the relocation including geopolitical and nationalistic reasons. Theoretical framework suggests that capital relocation is one of the effective tools of national identity development that is commonly used in post-socialist states. The paper suggests that Astana is the political elite’s project aimed at becoming a centerpiece of the nationalist nation-building strategy in Kazakhstan. The research contributes to the theory by investigating unrequited question of intersection of national identity and nationalism and built environment in post-soviet Asia.